2010
DOI: 10.1111/j.1365-2486.2010.02163.x
|View full text |Cite
|
Sign up to set email alerts
|

El Niño Southern Oscillation and climate trends impact reservoir water quality

Abstract: Low dissolved oxygen concentration in bottom layers of lakes and reservoirs usually indicates low water quality. In lakes, empirical models predicting anoxia are almost entirely based on the decay of plankton biomass, while in reservoirs recent findings suggest a prominent role of streamflow and load of organic carbon. This suggests a potential link between water quality in reservoirs and climate processes affecting streamflow. Here we support this hypothesis presenting evidence that both interannual climate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 40 publications
(50 reference statements)
2
35
0
Order By: Relevance
“…Land uses changes have a moderate role in this change, account for the 17%-27% of the observed trend. These estimations broadly coincide with results obtained by [16] for the nearby Ter Watershed using an independent approach. …”
Section: Hydrological Alterations Due To Global Changesupporting
confidence: 90%
“…Land uses changes have a moderate role in this change, account for the 17%-27% of the observed trend. These estimations broadly coincide with results obtained by [16] for the nearby Ter Watershed using an independent approach. …”
Section: Hydrological Alterations Due To Global Changesupporting
confidence: 90%
“…However, further evaluation of the relationship between ONI and reservoir TOC data is warranted. Recent research using long-term instrumented data found a relationship between ENSO phase, streamflow and reservoir dissolved oxygen content [58]. This supports the possible relationship between ENSO and reservoir water quality and indicates dissolved oxygen analysis at Converse Reservoir may be warranted.…”
Section: Effects Of Enso On Reservoir Nutrient Concentrationssupporting
confidence: 55%
“…Edwards and Thornes (1973) used regression, spectral, and cross-spectral techniques to find a strong annual cycle present in the water quality data in the River Stour, eastern England. Marce et al (2010) used spectral and wavelet techniques and found that the El Niño, streamflow, and reservoir oxygen content series oscillated in periods which coincided with the main El Niño variability modes.…”
Section: Non-water Mechanism Modelsmentioning
confidence: 97%